Modello logico e realizzazione di un Sistema Informativo Territoriale per la gestione selvicolturale - Foria, Federico (GEOmedia, 2013)
Logical model and implementation of a Geographic Information System for forest management. In this paper we present the realization of information tools aimed at a forest management to incr ease the protective functions of forests and soil conserv ation through GIS software. The Geographic Information System will aim to contain the maps as basis for the serv ices of monitoring, analysis and support to any form of interv ention. The article will refer to Arc GIS nomenclature for his technical and didactics importance but the same could be done with any other open sourc e software.